2020
DOI: 10.2478/tperj-2020-0008
|View full text |Cite
|
Sign up to set email alerts
|

Impact of using modern technology in training on sports performance

Abstract: Introduction: The close relationship between technology and sports is not necessarily modern. The ancient Greeks had the idea of sculpting and making an extraordinarily aerodynamic object in the form of a disc, an early masterpiece that has remained largely unchanged to this day.Purpose: This paper aims to show the importance of monitoring training using technological tools, so as to result in a beneficial effect on athletes.Materials and methods: In order to carry out this research, 32 athletes, boxing practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Human beings have entered the twenty-first century with the development of science and technology, the vigorous development of biological sciences, the rapid development of biomolecules and human genetics, and breakthroughs in human understanding of diseases. In today's increasingly scarce, especially the mismatch between high-quality medical resources and the people's medical needs, the contradiction between doctors and patients is constantly increasing [ 1 ]. In the doctor's diagnosis and treatment processing, due to personal negligence or lack of medical literacy, the patient's condition is delayed.…”
Section: Introductionmentioning
confidence: 99%
“…Human beings have entered the twenty-first century with the development of science and technology, the vigorous development of biological sciences, the rapid development of biomolecules and human genetics, and breakthroughs in human understanding of diseases. In today's increasingly scarce, especially the mismatch between high-quality medical resources and the people's medical needs, the contradiction between doctors and patients is constantly increasing [ 1 ]. In the doctor's diagnosis and treatment processing, due to personal negligence or lack of medical literacy, the patient's condition is delayed.…”
Section: Introductionmentioning
confidence: 99%
“…David and Popoli provided an approach to positive resilience training in dance classes that provides dancers with useful guidance related to key career inflection points (amateur to professional, professional to professional, and professional to retirement) to enhance their resilience [2]. Arnutu and Haniu demonstrated the importance of the use of monitoring technology tools for rehabilitation training, and based on the data analyzed, they confirmed that the use of technology to implement a monitoring training program will lead to improvements in the indicators pursued in the study [3]. Marcus examined the rehabilitation training programs of elite youth judo athletes throughout the annual training cycle, monitoring the training level of perceived exertion and the total duration of each training session [4].…”
Section: Related Workmentioning
confidence: 67%